2021
DOI: 10.1002/nop2.1136
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharps injuries among secondary and tertiary healthcare workers, Saudi Arabia

Abstract: Needlestick and sharps injuries (NSSIs) are accidental piercings of the body, sustained in association with the use of devices such as needles, ampoules and lancets that are used in healthcare settings, and they constitute an occupational hazard for healthcare workers (HCWs;Zhang et al., 2009). These injuries may lead to the development of serious diseases among HCWs. Global estimates show that more than 35 million HCWs sustain NSSIs, annually; according to the Centers for Disease Prevention and Control, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Over one-fourth (27.9%) of HCWs had at least one history of NSI during the last 12 months, with nursing staff having the highest incidence. These findings are in line with the published results from China (23.2%) and Saudi Arabia, where a quarter (24.9%) of HCWs reported the incidence of NSI [ 29 , 30 ]. However, other LMICs, such as Iran (42.5%) and Nigeria (51.0%), revealed higher NSI history among HCWs [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Over one-fourth (27.9%) of HCWs had at least one history of NSI during the last 12 months, with nursing staff having the highest incidence. These findings are in line with the published results from China (23.2%) and Saudi Arabia, where a quarter (24.9%) of HCWs reported the incidence of NSI [ 29 , 30 ]. However, other LMICs, such as Iran (42.5%) and Nigeria (51.0%), revealed higher NSI history among HCWs [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, we found a significantly higher incidence of NSIs among HCWs who worked in secondary healthcare hospitals than tertiary hospitals (16.3 vs. 10.1%). Similarly, the needle stick and sharps injuries rates were 30 and 14% in secondary and tertiary hospitals, respectively in a study conducted in Jazan ( 42 ). The difference in the health services, numbers, and types of procedures in addition to the number of admissions may explain the difference in incidence between secondary and tertiary healthcare hospitals in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Data from 2014 to 2018 stated that there were around 16.000 health workers infected with hepatitis B and 66.000 infected with hepatitis C, while HIV transmission due to needle sticks was around 1.000 cases (Alfulayw et al, 2021). The Center for Disease Control and Prevention (CDC) in the United States in its statistics with the European Agency for Safety and Health at Work (EU-OSHA) revealed that there were around 35.000 to 1 million cases of needle sticks occurring in health services in the last 10 years (Makeen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%